Effects of high dose inhaled beclomethasone dipropionate, 750 micrograms and 1500 micrograms twice daily, and 40 mg per day oral prednisolone on lung function, symptoms, and bronchial hyperresponsiveness in patients with non-asthmatic chronic airflow obstruction. - Weir, D C (1993)
BACKGROUND--The effect of treatment with inhaled corticosteroids in patients with non-asthmatic chronic airflow obstruction is still disputed. Whether any physiological improvements seen are accompanied by changes in bronchial responsiveness and symptoms and quality of life is also still unclear. METHODS--A sequential placebo controlled, blinded parallel group study investigating the effect of three weeks of treatment with inhaled beclomethasone dipropionate (BDP), 750 micrograms or 1500 micrograms twice daily, and oral prednisolone, 40 mg per day, was carried out in 105 patients with severe non-asthmatic chronic airflow obstruction (mean age 66 years, mean forced expiratory volume in one second (FEV1) 1.05 litres [40% predicted], geometric mean PD20 0.52 mumol). End points assessed were FEV1, forced vital capacity (FVC), and peak expiratory flow (PEF), bronchial responsiveness to inhaled histamine, and quality of life as measured by a formal quality of life questionnaire. RESULTS--Both doses of BDP produced equivalent, small, but significant improvements in FEV1 (mean 48 ml), FVC (mean 120 ml), and PEF (mean 12.4 l/min). The addition of oral prednisolone to the treatment regime in two thirds of the patients did not produce any further improvement in these parameters. Inhaled BDP produced a treatment response in individual patients (defined as an improvement in FEV1, FVC, or mean PEF of at least 20% compared with baseline values) more commonly than placebo (34% v 15%). The two doses of BDP were equally effective in this respect and again no further benefit of treatment with oral prednisolone was noted. Treatment with BDP for up to six weeks did not affect bronchial responsiveness to histamine. Small but significant improvements were seen in dyspnoea during daily activities, and the feeling of mastery over the disease. CONCLUSIONS--High dose inhaled BDP is an effective treatment for patients with chronic airflow obstruction not caused by asthma. Both objective and subjective measures show improvement. Unlike asthma, no improvement in bronchial responsiveness was detected after six weeks of treatment.